A versatile modification strategy for functional non-glutaraldehyde cross-linked bioprosthetic heart valves with enhanced anticoagulant, anticalcification and endothelialization properties. (1st April 2023) - Yu, Tao; Pu, Hongxia; Chen, Xiaotong; Kong, Qunshou; Chen, Chong; Li, Gaocan; Jiang, Qing; Wang, Yunbing
Abstract: Valvular heart disease is a major threat to human health and transcatheter heart valve replacement (THVR) has emerged as the primary treatment option for severe heart valve disease. Bioprosthetic heart valves (BHVs) with superior hemodynamic performance and compressibility have become the first choice for THVR, and more BHVs have been requested for clinical use in recent years. However, several drawbacks remain for the commercial BHVs cross-linked by glutaraldehyde, including calcification, thrombin, poor biocompatibility and difficulty in endothelialization, which would further reduce the BHVs' lifetime. This study developed a dual-functional non-glutaraldehyde crosslinking reagent OX-VI, which can provide BHV materials with reactive double bonds (CC) for further bio-function modification in addition to the crosslinking function. BHV material PBAF@OX-PP was developed from OX-VI treated porcine pericardium (PP) after the polymerization with 4-vinylbenzene boronic acid and the subsequent modification of poly (vinyl alcohol) and fucoidan. Based on the functional anti-coagulation and endothelialization strategy and dual-functional crosslinking reagent, PBAF@OX-PP has better anti-coagulation and anti-calcification properties, higher biocompatibility, and improved endothelial cells proliferation when compared to Glut-treated PP, as well as the satisfactory mechanical properties and enhanced resistance effect to enzymatic degradation, making it a promising candidate in the clinical application of BHVs. Statement of significance: Transcatheter heart valve replacement (THVR) has become the main solution for severe valvular heart disease. However, bioprosthetic heart valves (BHVs) used in THVR exhibit fatal drawbacks such as calcification, thrombin and difficulty for endothelialization, which are due to the glutaraldehyde crosslinking, resulting in a limited lifetime to 10-15 years. A new non-glutaraldehyde cross-linker OX-VI has been designed, which can not only show great crosslinking ability but also offer the BHVs with reactive double bonds (CC) for further bio-function modification. Based on the dual-functional crosslinking reagent OX-VI, a versatile modification strategy was developed and the BHV material (PBAF@OX-PP) has been developed and shows significantly enhanced anticoagulant, anti-calcification and endothelialization properties, making it a promising candidate in the clinical application of BHVs. Graphical Abstract: Image, graphical abstract